FemA based drug design for potentiation of B-lactam antibiotics against Methicillin Resistant Staphylococcus aureus - Singhal, Divya (My University, 2019)
The present study was oriented to identify the resistance modifying agent (RMA) for β-lactam antibiotics, Penicillin and Oxacillin against Methicillin resistant Staphylococcus aureus (MRSA). Initially, identification of RMA’s was based on inhibitors of FemA protein’s structure, which is a novel drug target and has not been exploited so far in antibiotic drug development, using computational tools by virtual library of compounds. Catechin Gallate (CG) was selected as the inhibitor of FemA protein from in silico studies which comprised of docking, interaction, toxicity and checking of Lipinski violations. Subsequently to identifying CG as a lead molecule from in silico studies, its antibacterial property in presence and absence of antibiotics Oxacillin and Penicillin was carried out to arrive to MIC and FIC index of the antibiotic combinations. Further time kill kinetics and mucopolysaccharide content of the test and control organisms was carried out by nLC-MS in the three standard isolates of S. aureus. Three synergistic formulations viz formulation of 62.5 μg/ml oxacillin with 7.8 μg/ml of CG, 62.5 μg/ml oxacillin with 31.25 μg/ml of CG and 125 μg/ml of oxacillin with 7.8 μg/ml of CG were found to potentiate oxacillin against three isolates of S. aureus viz. NCTC 6571, MTCC 737 and MTCC 96, while one synergistic formulation of 2000 μg/ml penicillin with 7.8 μg/ml of CG was found to be effective against NCTC 6571 Reduction of more than 50% peak area in concentration of muropeptides of test formulations compared to their control, indicates the modulation of functional expression of FemXAB proteins by CG the selected inhibitor of FemA protein. Subsequently, β-lactam antibiotic efficiency has been increased in MRSA strains. With the use of CG, possibly due to inhibition of FemXAB protein as evident from change in muropepides content. Hence, the present study establishes the potential of Catechin Gallate as potentiator of β-lactam antibiotics against MRSA in vitro and warrants extensive studies on clinical isolates and their muropeptides composition.
Keywords: MRSA; B-lactam; Staphylococcus; Resistance; Catechin gallate